The role of technology in shaping online learning effectiveness in engineering higher education: a theoretical perspective - P J, Thomas; Hieng, Ho Lau; Lim, Bibiana Chiu-Yiong; Kapoor, Ajay (Penerbit UiTM (UiTM Press), 2026)
The digitization of engineering education is reshaping the design, delivery, and effectiveness of online learning environments. This conceptual paper examines how emerging educational technologies-such as artificial intelligence, immersive technologies, learning analytics, and cloud-based platforms-can be systematically integrated to enhance learning effectiveness in online engineering education. Drawing on an integrative review of contemporary literature and established learning theories, the study proposes a multidimensional framework comprising five interrelated dimensions: technological infrastructure, pedagogical design, user experience design, feedback and learning analytics, and support systems. Grounded in constructivism, connectivism, cognitive load theory, self-determination theory, and activity theory, the framework explains how coordinated technological and pedagogical alignment can improve learner engagement, motivation, collaboration, and performance. By moving beyond tool-centric approaches, the paper offers a theory-driven lens to guide educators, administrators, and policy makers in designing effective and sustainable online engineering learning environments and provides a foundation for future empirical validation.